Influence of Maturity and Physiological Status of Woody Cuttings: Limits and Promises to Ensure Successful Cloning - Puri, Sunil; Khara, Amarjeet (Indian Forester, 1992)
Vegetative propagation methods make possible the production of exact copies of trees selected for superior characteristics. These methods include conventional techniques such as rooting cuttings, grafting, and air-layering, as well as newer plant tissue culture methods that include embryo or cotyledon culture, shoot tip culture, and callus and cell culture. The most commonly practiced technique is rooting stem cuttings and this is being discussed in detail. Rooting ability of the cutting is influenced by genetic component, physiological state of the cutting and the environment in which the cutting is planted. Hormonal changes occurred with season, but these are complex and are not yet well understood. Depletion of metabolic food reserves, particularly starch, takes place rapidly during rooting. Alleviation of moisture stress is critical to rooting of cuttings and high humidities are required. Cuttings take up water through the cut base of the shoot and pre-soaking of cuttings stimulated rooting even in the drier soil moisture conditions. Initially the water potential of cuttings decreased with time and with the formation of roots it stabilized. In the application of the results presented, it is envisaged that both physiological and environmental factors influence rooting to stem cuttings. The biological limitations, particularly in relation to number of clones for afforestation purposes, is being discussed.